The impact of green marketing on a consumer's purchase decision. - Ong, Jun Han. (2011)
Recently, green marketing efforts by both firms and non-profit organisations in the form of advertisements, type of products offered, Corporate Social Responsibility (CSR) programmes have been gaining prominence. In this report, we would be looking at various types of green marketing efforts individually and investigate their effects on the purchase decisions of a regular consumer of a green product. From analysing our survey research, we conclude that amongst other green marketing tools such as pricing, highlighting of green attributes in advertisements, etc., presence of the green labels on a product is the most effective tool to influence a consumer to purchase a green product. When used in an optimal mix of marketing tools discussed in the paper, marketers could very successfully increase purchases of green products for the commercial motive of profit-making or the social motive of shifting responsibility of environmental care onto consumers.